ANALISIS PENGARUH PERILAKU PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI SEBAGAI VARIABEL MODERATING - Stevanus Tri Anggoro; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to analyze the effect of tax avoidance behavior on firm value by considering transparancy as a moderating variable. Tax avoidance as an independen variable is measured by book-tax-difference (BTD) value. Firm value and agency cost as dependen variable are measured by Tobins q and STA value. Transparency as moderating variable measured by the ratio that takes intoitem contained in financial statements under the provisions of GCG self assessment int 2010. This research uses leverage as a control variabel. The sample of this research is manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2013. The sampling method in this research is purposive sampling. The analysis techique in this study using multiple regression analysis. Overall, the results show that tax avoidance behavior has significant positive effects on the firm value. Tax avoidance has positive effects on the agency cost. And transparency can moderate the effect of tax avoidance on firm value.